Randomblocks: A transparent, verifiable blockchain-based system for random numbers - Christodoulou, Klitos; Chatzichristofis, Savvas A.; Sirakoulis, Georgios Ch; Christodoulou, Panayiotis (My University, 2019)
Games-of-chance require high-levels of trust between participants that is often uncertain and difficult to enforce. The unique characteristics introduced by the blockchain technology can be leveraged to inform a verifiable but transparent pseudo-random generation process that at the same time eliminates the need of an external trustee service or oracle to guarantee the fair execution of the process. We propose a process that builds on a one-dimensional Cellular Automaton (CA) where the evolution of the CA aligns to the evolution of a blockchain. Given an initial seed defined as the point in time where the evolution of the CA is triggered, the set of transition rules, along with the finite number of evolution steps, any external oracle is able to verify and backtrack (but not predict) the outcome of the process. The effectiveness of the implemented system is confirmed by the use of various statistical testing suites that confirm the existence of a set of statistical properties required to produce sufficient pseudo-random number sequences.
Keywords: Blockchain; Pseudo-random number generation; Cellular automata